The use of direct coercion during the management of a patient with paranoid schizophrenia - case report - Fąfara, Anna; Marć, Małgorzata; Aebisher, David; Fudali, Krzysztof; Krakowiak-Burdzy, Anna; Lesiak, Aneta; Zięba, Klaudia (Medical Studies/Studia Medyczne, 2022)
In a situation of increased aggression from a patient, which creates a danger and a threat to their own health and to other patients and staff, direct coercion is used. Such intervention is undertaken when it is necessary to protect the patient’s life or health. The aim of this study is to show the specifics of care for a patient in whom an assessment of mental health during the period of intensification of symptoms of paranoid schizophrenia indicated the legitimacy of the use of direct coercion. The paper describes an individual case of a mechanically immobilized patient. To collect data about the patient, the following research techniques were used: interview, observation, measurement, and documentation analysis. The following research tools were also used in the work: interview questionnaire, a card for the application of direct coercion against a person staying in a psychiatric hospital or other medical institution or in an organizational unit of social assistance, the Modified Explicit Aggression Scale – MOAS, and the Courtauld Emotional Control Scale (CECS). Mechanical immobilization is unpleasant for both the patient and the staff. Nevertheless, it is indispensable in certain cases. Compliance with the law makes it impossible to commit abuses against a patient who has been mechanically immobilized.